FEMINIST INTERPRETATIONS OF ACTION AND THE PUBLIC IN HANNAH ARENDT’S THEORY - Noémi BÍRÓ (Studia Universitatis Babeș-Bolyai. Philosophia, 2020)
Feminist Interpretations of Action and the Public in Hannah Arendt’s Theory. Arendt’s typology of human activity and her arguments on the precondition of politics allow for a variety in interpretations for contemporary political thought. The feminist reception of Arendt’s work ranges from critical to conciliatory readings that attempt to find the points in which Arendt’s theory might inspire a feminist political project. In this paper I explore the ways in which feminist thought has responded to Arendt’s definition of action, freedom and politics, and whether her theoretical framework can be useful in a feminist rethinking of politics, power and the public realm.